A Method for Direct Monitoring of Atorvastatin Adherence in Cardiovascular Disease Prevention: Quantification of the Total Exposure to Parent Drug and Major Metabolites Using 2-Channel Chromatography and Tandem Mass Spectrometry. Issue 1 (February 2019) - Vethe, Nils Tore; Munkhaugen, John; Andersen, Anders M.; Husebye, Einar; Bergan, Stein
Abstract : Background: Low adherence to statin therapy remains a public health concern associated with poor prognosis in cardiovascular disease patients. A feasible method for statin adherence monitoring in clinical practice has yet to be developed. In this article, we describe a novel method designed for the direct monitoring of atorvastatin adherence based on the sum of parent drug and major metabolites in blood samples. Methods: Acid and lactone forms of atorvastatin, 2-OH-atorvastatin, and 4-OH-atorvastatin were assayed. Plasma proteins were precipitated with an acidified mixture of methanol, acetonitrile, and aqueous zinc sulfate, and the supernatant was analyzed with 2-channel reversed-phase chromatography coupled to tandem mass spectrometry. Assay validation was performed according to the guidelines provided by the European Medicines Agency and the US Food and Drug Administration. Results: The effective run time was 1 minute and 45 seconds per sample. Mean accuracy ranged from 92% to 110%, and coefficients of variation were ⩽8.1% over the measurement ranges for individual compounds. The sum of acids and corresponding lactones was stable in clinical plasma samples kept at ambient temperature for up to 6 days after blood sampling (mean sum within 96.6%–101% of baseline). Conclusions: A fast and reliable assay for the quantification of atorvastatin and its 5 major metabolites in clinical blood samples is reported. Limitations of preanalytical stability were solved using the sum of the acid and lactone forms. The assay is feasible for implementation in clinical practice, and the sum of parent drug and metabolites may be used for direct monitoring of atorvastatin adherence.